Food security, fertility differentials and land degradation in Sub-Saharan Africa: A dynamic framework - Maria Winkler-Dworak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2003)
We study the impact of differential fertility levels for the food-insecure and foodsecure population on the long-run values of the population distribution and resources in a descriptive model, where the food security states are determined by a historically given food distribution and by the endogenous food production with resources and labor as inputs. Furthermore, we assume that the resource stock is reduced by povertydriven environmental degradation. Moreover, we incorporate nutritional effects on labor productivity and mortality. By applying local bifurcation theory, we show that the model may exhibit multiple equilibria. Furthermore, the orbits of resources and the population distribution may be characterized by quasi-periodic behavior. Sustainable development in terms of approaching a steady state with positive values of resources and food-secure population is only promoted by low fertility levels of the food-insecure and food-secure population.
Keywords: C62; I32; Q01; 330; Food Distribution; Fertility; Land Degradation; Dynamic Systems; Multiple Equilibria; Local Bifurcation